Biological control of ticks - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1991)
Parastic wasps, fungi and chickens may soon be used by farmers to control ticks. They may not completely replace acaricides, but they could play a significant role in reducing the need to dip or spray livestock. Scientists at the International...